What drives the international transfer of climate change mitigation technologies? Empirical evidence from patent data - Antoine Dechezleprêtre; Matthieu Glachant; Yann Ménière (Fondazione Eni Enrico Mattei (FEEM), 2010)
Using patent data from 66 countries for the period 1990-2003, we characterize the factors which promote or hinder the international diffusion of climate-friendly technologies on a global scale. Regression results show that technology-specific capabilities of the recipient countries are determinant factors. In contrast, the general level of education is less important. We also show that restrictions to international trade-e.g., high tariff rates-and lax intellectual property regimes negatively influence the international diffusion of patented knowledge. A counter-intuitive result is that barriers to foreign direct investments can promote transfers. We discuss different possible interpretations.
Keywords: O33; O34; Q54; 330; Climate Change; Technology Diffusion; Technology Transfer; Klimaschutz; Technologietransfer; Innovationsdiffusion; Außenhandelsbeschränkung; Welt